Pemberdayaan Masyarakat untuk Peningkatan Manajerial Desa Wisata di Kalurahan Umbulrejo, Kapanewon Ponjong, Kabupaten Gunungkidul - Hafida, Siti Hadiyati Nur; Wardhani, Puspita Indra; Dewi, Ratih Puspita; Hermawan, Hardika Dwi; Taufiq, Muhammad Luqman (Abdi Geomedisains, 2025)
Umbulrejo Village has interesting and unique natural tourism potential. This village has officially become a tourist village and has had a pokdarwis (tourism awareness group); however, after the pandemic, the number of tourists coming was very small, so it had an impact on the economy of the community in Umbulrejo Village. Based on the potential and problems experienced by the Umbulrejo pokdarwis, it is known that the capacity of human resources in managing the Umbulrejo Tourism Village is very limited, so that tourism management is not optimal. The purpose of this community service activity is to increase the managerial capacity of the tourist village for the Umbulrejo pokdarwis. This community empowerment activity is carried out through three stages, namely the awareness and behavior formation stage, the transformation stage, and the intellectual enhancement stage. From the results of this community empowerment activity, the following results were obtained: 1) the awareness and behavior formation stage, namely, the community around the Umbulrejo Tourism Village must start building networks and working together as a team, especially between homestay providers and pokdarwis administrators. This stage has been carried out well, and intensive communication has been realized between pokdarwis administrators and homestay providers; 2) the transformation stage, namely, the community begins to integrate local culture into tourism activities. The community prepares a tour package that is integrated with the appearance of local culture in (Umbulrejo Tourism Village; 3) the intellectual development stage, namely the creation of social media for promotion with an attractive and informative design. The Pokdarwis management already has several social media accounts that can be used as promotional media. Through this community service activity, the management of Umbulrejo Tourism Village is expected to maintain the sustainability of tourism in Umbulrejo Village.